Development, hotspots and trend directions of groundwater numerical simulation: A bibliometric and visualization analysis - Liu Yang; Yan-pei Cheng; Xue-ru Wen; Jun Liu (Journal of Groundwater Science and Engineering)
Groundwater is a vital component of the hydrological cycle and essential for the sustainable development of ecosystems. Numerical simulation methods are key tools for addressing scientific challenges in groundwater research. This study uses bibliometric visualization analysis to examine the progress and trends in groundwater numerical simulation methods. By analyzing literature indexed in the Web of Science database from January 1990 to February 2023, and employing tools such as Citespace and VOSviewer, we assessed publication volume, research institutions and their collaborations, prolific scholars, keyword clustering, and emerging trends. The findings indicate an overall upward trend in both the number of publications and citations concerning groundwater numerical simulations. Since 2010, the number of publications has tripled compared to the total before 2010, underscoring the increasing significance and potential of numerical simulation methods in groundwater science. China, in particular, has shown remarkable growth in this field over the past decade, surpassing the United States, Canada, and Germany. This progress is closely linked to strong national support and active participation from research institutions, especially the contributions from teams at Hohai University, China University of Geosciences, and the University of Science and Technology of China. Collaboration between research teams is primarily seen between China and the United States, with less noticeable cooperation among other countries, resulting in a diverse and dispersed development pattern. Keyword analysis highlights that international research hotspots include groundwater recharge, karst water, geothermal water migration, seawater intrusion, variable density flow, contaminant and solute transport, pollution remediation, and land subsidence. Looking ahead, groundwater numerical simulations are expected to play a more prominent role in areas such as climate change, surface water-groundwater interactions, the impact of groundwater nitrates on the environment and health, submarine groundwater discharge, ecological water use, groundwater management, and risk prevention.